An introduction to community & public health - McKenzie, James F.; Pinger, R. R.; Seabert, Denise (Jones & Bartlett Learning, 2018)
With an emphasis on developing the knowledge and skills necessary for a career in health education and health promotion, this best selling introductory text covers such topics as epidemiology, community organizations, program planning, minority health, mental health, environmental health, drug use and abuse, safety, and occupational health.